2000
DOI: 10.1002/(sici)1097-0290(20000220)67:4<465::aid-bit10>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide uptake efficiency by outdoor microalgal cultures in tubular airlift photobioreactors

Abstract: The influence of solar irradiance and carbon dioxide molar fraction of injected CO2–air mixtures on the behavior of outdoor continuous cultures of the microalga Phaeodactylum tricornutum in tubular airlift photobioreactors was analyzed. Instantaneous solar irradiance, pH, dissolved oxygen, temperature, biomass concentration, and the mass flow rates of both the inlet and outlet oxygen and carbon with both the liquid and gas phases were measured. In addition, elemental analysis of the biomass and the cell‐free c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 29 publications
3
26
0
4
Order By: Relevance
“…Because the k * a * value in the loop was low, pure carbon dioxide was indicated for injection to improve the gas}liquid mass transfer driving force and prevent carbon limitations (Camacho Rubio et al, 1999). However, injecting pure carbon dioxide can a!ect local pH values and culture productivity (Olaizola, Duerr, & Freeman, 1991;Mazzuca Sobczuk et al, 2000). This e!ect may be reduced by diluting the injected gas with air or nitrogen.…”
Section: Hydrodynamic and Mass Transfer Characterizationsupporting
confidence: 79%
“…Because the k * a * value in the loop was low, pure carbon dioxide was indicated for injection to improve the gas}liquid mass transfer driving force and prevent carbon limitations (Camacho Rubio et al, 1999). However, injecting pure carbon dioxide can a!ect local pH values and culture productivity (Olaizola, Duerr, & Freeman, 1991;Mazzuca Sobczuk et al, 2000). This e!ect may be reduced by diluting the injected gas with air or nitrogen.…”
Section: Hydrodynamic and Mass Transfer Characterizationsupporting
confidence: 79%
“…On average, the net amount of fixated CO 2 (in g CO 2 g − 1 Table 1 Average daily photon fluxes, net volumetric productivities, yields of biomass on light and CO 2 production at night for the 3 different night temperatures. a T night (°C) biomass) by T. suecica was 1.53 g g −1 , which is in accordance with the CO 2 requirement of the algal biomass [30]. The CO 2 uptake was actually expected to be higher.…”
Section: Resultsmentioning
confidence: 99%
“…Effect of CO 2 concentration on growth Sobczuk et al [10] reported that the yield of biomass increased significantly when the CO 2 molar fraction in the injected gas was reduced. They also showed that with less CO 2 in the injected gas, the O 2 generation rate and the CO 2 consumption rate were greater.…”
Section: Resultsmentioning
confidence: 99%